UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN MINAT SISWA MEMILIH SMP NEGERI 21 REJANG LEBONG - Widia Kartika; Ngadri Yusro; Siswanto Siswanto (Institut PTIQ Jakarta, 2020)
This study aimed to find out a depiction of principal’s efforts to increase community’s interest in sending their children to SMP Negeri 21 Rejang Lebong in the midst of competition wherein there are many schools in the region. This study used a qualitative approach with the school principal and teachers as the key informants. This study used observation, interviews, and documentation techniques to collect the data. After the data were collected, the data were subsequently analyzed using Miles’ et al approach extending to data reduction, data presentation, and verification as well as drawing conclusions. This study revealed that so that the efforts made to by increase the interest of new students attending SMPN 21 Rejang Lebong included: Improving the quality of schools in terms of both learning and services, completing school facilities and infrastructure, promoting schools by distributing brochures, providing information to neighboring teachers and making billboard displayed in front of schools presenting the school's superior activities.